The Dilemma - Krishnaveni, Dr. R.; Deepa, R (Journal of Contemporary Research in Management (JCRM), 2013)
Team based work culture is becoming predominant in today's work environment, especially IT organizations. The work environment is characterized by tight deadlines, work pressures and tough competition. Career progression is ensured only through sustained performance. This case describes a team based work environment in an organization. Specifically, it brings out the response of a male and female employee of the organization towards a work place issue. The case ends up by provoking the readers to analyze the differences in response.